Case report: Thrombotic microangiopathy concomitant with macrophage activation syndrome in systemic lupus erythematosus refractory to conventional treatment successfully treated with eculizumab - Yamaguchi, Makoto; Mizuno, Masashi; Kitamura, Fumiya; Iwagaitsu, Shiho; Nobata, Hironobu; Kinashi, Hiroshi; Banno, Shogo; Asai, Akimasa; Ishimoto, Takuji; Katsuno, Takayuki; Ito, Yasuhiko (Frontiers in Medicine, 2023)
Thrombotic microangiopathy (TMA) is a rare but life-threatening complication of systemic lupus erythematosus (SLE). Macrophage activation syndrome (MAS) is also a rare, life-threatening hyperinflammatory condition that is comorbid with SLE. However, the association between TMA and MAS in patients with SLE has rarely been assessed, and the difficulty of diagnosing these conditions remains prevalent. The efficacy of eculizumab has been reported for SLE patients whose conditions are complicated with TMA. However, no study has investigated the therapeutic efficacy of eculizumab for TMA concomitant with SLE-associated MAS. Herein, we report the first case of TMA concomitant with SLE-associated MAS that was initially refractory to conventional immunosuppressive therapy but showed remarkable recovery after eculizumab treatment. Furthermore, we evaluated serum syndecan-1 and hyaluronan levels, which are biomarkers of endothelial damage. We found that these levels decreased after the administration of eculizumab, suggesting that TMA was the main pathology of the patient. This case illustrates that it is important to appropriately assess the possibility of TMA during the course of SLE-associated MAS and consider the use of eculizumab as necessary.